2004
DOI: 10.1097/01.aog.0000119222.40241.fb
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder in Pregnancy: Prevalence, Risk Factors, and Treatment

Abstract: II-2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
2
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(65 citation statements)
references
References 18 publications
2
60
2
1
Order By: Relevance
“…Gold, Milan, Mayall, and Johnson (1994) reported higher TSC-40 averages in their study of 654 female undergraduate students, with average scores of 70.4 for participants who reported a history of child sexual abuse, 73.5 among participants with a reported history of adult sexual assault, and 77.4 for participants who reported a history of both childhood sexual abuse and adult sexual assault. A participant sample exhibiting higher trauma symptoms might report more negative effects on their current attachment to their unborn child, particularly those with severe PTSD or similar psychiatric symptomatology (Loveland Cook et al, 2004;Seng et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gold, Milan, Mayall, and Johnson (1994) reported higher TSC-40 averages in their study of 654 female undergraduate students, with average scores of 70.4 for participants who reported a history of child sexual abuse, 73.5 among participants with a reported history of adult sexual assault, and 77.4 for participants who reported a history of both childhood sexual abuse and adult sexual assault. A participant sample exhibiting higher trauma symptoms might report more negative effects on their current attachment to their unborn child, particularly those with severe PTSD or similar psychiatric symptomatology (Loveland Cook et al, 2004;Seng et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In one of the few studies to date investigating the prevalence, risk factors, and treatment of PTSD among pregnant women, Loveland Cook et al (2004) reported that 7.7% of the 744 pregnant women surveyed met diagnostic criteria for PTSD (APA, 1994). Comorbid disorders were common among their participants, with results suggesting that women with PTSD were five times more likely to have a major depressive episode and three times more likely to have a generalized anxiety disorder.…”
Section: Trauma and Pregnancymentioning
confidence: 99%
“…Gold, Milan, Mayall, and Johnson (1994) reported higher TSC-40 averages in their study of 654 female undergraduate students, with average scores of 70.4 for participants who reported a history of child sexual abuse, 73.5 among participants with a reported history of adult sexual assault, and 77.4 for participants who reported a history of both childhood sexual abuse and adult sexual assault. It is possible that a sample exhibiting higher trauma symptoms might report more negative effects from participation in trauma-focused research particularly those with severe PTSD or similar psychiatric symptomatology (Loveland Cook et al, 2004;Seng et al, 2004). The differences found between pregnant women participants who indicated that research participation was personally meaningful and participants who indicated that participation was not personally meaningful suggests that participants with greater lifetime trauma exposure and higher trauma symptoms may perceive more benefits associated with trauma-focused research participation.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve studies establishing the prevalence of anxiety disorders in the perinatal period were identified (Table 7 [ 42,97,128,[206][207][208][209][210][211][212][213][214] In addition to the studies listed in Table 7, a number of studies have looked specifically at the incidence of postnatal PTSD with childbirth specified as the traumatic event [207,212,[215][216][217][218]. These studies, assessing for childbirth-specific PTSD occurring anywhere from 4 weeks to 1 year postpartum, found an incidence ranging from 0 to 6.9% with a mean of 3.8%.…”
Section: Anxiety Disordersmentioning
confidence: 99%